1974
DOI: 10.1021/jo00921a015
|View full text |Cite
|
Sign up to set email alerts
|

Studies of chemical exchange by nuclear magnetic resonance. IX. Rotation about the amide bond in N,N-dimethylformamide

Abstract: A-(Diethylphosphonyl)succinimide. This material separated from solution (92% N.A., 81% I.A.) during reaction as a white solid which was purified by recrystallization from methanol: mp 57-60°( lit.2 mp 60-62°); ir rmax (Nujol) 1730 (0=0),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…The experimental rotation barrier of DMF ( 1) is 91.2 kJ mol À1 in solution 12 and 85.8 kJ mol À1 in the gas-phase, 13 which compares well with our values (either 1c or 1d). Many theoretical studies have been published where values close to the experimental ones have been reported.…”
Section: Geometry and Barrierssupporting
confidence: 83%
“…The experimental rotation barrier of DMF ( 1) is 91.2 kJ mol À1 in solution 12 and 85.8 kJ mol À1 in the gas-phase, 13 which compares well with our values (either 1c or 1d). Many theoretical studies have been published where values close to the experimental ones have been reported.…”
Section: Geometry and Barrierssupporting
confidence: 83%
“…For compounds bearing electron‐donating functionalities ( 3d and 3e ) distinct AA′XX′ coupling patterns with four pseudo‐triplets for the eight C 5 H 4 protons are observable, however, with increasing electron‐withdrawing character of the substituents R the line‐width of the signals increases and hence no coupling could be observed. As this line broadening may be a result of an exchange process of the orientation at the nitrogen atom, dynamic 1 H NMR studies have been carried out 28. Upon heating 3a – 3e to 100 °C in d 7 ‐toluene a coalescence of the ferrocenyl resonances was observed for all compounds.…”
Section: Resultsmentioning
confidence: 99%
“…151 The Israeli Supreme Court's integrated and comparative way of examining constitutional law against international law, particularly in the Arjoub, Mustafa, Mar'ab and Public Committee Against Torture cases, is somewhat similar to the global due process model proposed by Gerald Neuman, although the Court has not formulated its reasoning to define a principled approach. 152 Neuman proposes examining whether constitutional rights are also part of international law (as norms that constitute jus cogens or obligate the state by virtue of international conventions) in order to decide whether they are appropriate for extraterritorial application. This way, international law serves as a yardstick for the universal recognition of these rights, and for the expectation of reciprocity from other states in applying the same rights.…”
Section: ]mentioning
confidence: 99%